Giomer composite compared to glass ionomer in occlusoproximal ART restorations of primary molars: 24-month RCT - Olegário da Costa, Isabel (My University, 2022)
Background Occlusoproximal restorations of primary molars usually fail, so it is necessary to investigate new materials that may overcome this challenge. Thus, this trial aimed to evaluate the longevity of occlusoproximal ART restorations in primary molars using a glass ionomer cement – GIC (Equia Forte® – GC Corp) and a Giomer resin composite – GCR (Beautifil Bulk Restorative® – Shofu Inc) after 24 months. Methods One hundred and eighty-two (182) children aged from 4 to 8 years were selected and randomly assigned to GIC or GCR. A paediatric dentist treated them in the school setting in Cerquilho, Brazil, and the restorations were assessed after 3, 6, 12, 18 and 24 months. The primary outcome was the restoration survival, evaluated using the Kaplan–Meier and superiority Cox regression analyses. Intention to treat (ITT) was performed as a sensitivity analysis using superiority test P value and confidence interval (CI = 95%). Independent variables included gender, age, molar, jaw, cavity volume and caries experience. Results The restoration survival after 24 months was GIC = 58.1% and GCR = 49.1% (HR = 1.24; CI = 0.97–1.59). ITT analysis showed a success of GIC = 61.1% and GCR = 52.2% (RR = 1.17; CI = 0.91–1.52). The superiority hypothesis was not proved in both analyses (P > 0.05). Conclusion GCR does not have superior longevity than GIC in occlusoproximal ART restorations of primary molars.
Keywords: Primary teeth; Atraumatic Restorative Treatment; Giomer; Glass ionomer cement; Paediatric dentistry; Nanoscience & Materials; Dentistry; Restorative dentistry and materials science